Boosting EFL Speaking Skills through Role Play: Evidence from Seventh Grade Students - Sukmara, Edi; Friatin, Lilies Youlia; Tarwana, Wawan (Universitas Galuh, 2025)
This study investigates the effectiveness of role play in enhancing English as a Foreign Language (EFL) speaking skills among seventh-grade students at SMPN 1 Panawangan, Ciamis. Recognizing speaking as a central yet challenging skill for EFL learners, particularly in Indonesian classrooms where conventional teacher-centered methods prevail, the study sought to determine whether role play could provide more meaningful and engaging communicative opportunities. Employing a true experimental design with a pre-test–post-test control group, 64 students were randomly assigned into experimental and control groups. The experimental group received six sessions of role play–based instruction, while the control group was taught through traditional drills and guided dialogues. Students’ speaking performance was assessed in terms of fluency, vocabulary, pronunciation, and grammar, with inter-rater scoring ensuring reliability. Findings revealed that while both groups showed improvement, the experimental group demonstrated significantly higher gains in overall speaking performance, as confirmed by independent samples t-test results (t-observed = 3.456 > t-table = 2.000, p < 0.05). Role play not only enhanced linguistic competence but also boosted learners’ confidence and reduced speaking anxiety by creating a supportive, interactive environment. These results align with the principles of Communicative Language Teaching (CLT) and socio-constructivist theory, highlighting role play as a learner-centered strategy that fosters authentic communication and equal participation. The study concludes that role play is an effective pedagogical tool for improving junior high school students’ speaking abilities and recommends its integration into EFL curricula to promote fluency, confidence, and communicative competence in real-life contexts.